Using value stream mapping technique through the lean production transformation process: An implementation in a large-scaled tractor company - Mehmet Rıza Adalı; Alper Kiraz; Uğur Akyüz; Betül Halk (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2017)
Today’s world, manufacturing industries have to continue their development and continuity in more competitive environment via decreasing their costs. As a first step in the lean production process transformation is to analyze the value added activities and non-value adding activities. This study aims at applying the concepts of Value Stream Mapping (VSM) in a large-scaled tractor company in Sakarya. Waste and process time are identified by mapping the current state in the production line of platform. The future state was suggested with improvements for elimination of waste and reduction of lead time, which went from 13,08 to 4,35 days. Analysis are made using current and future states to support the suggested improvements and cycle time of the production line of platform is improved 8%. Results showed that VSM is a good alternative in the decision-making for change in production process.